Fenomena Crowding-Out, Overshooting, dan Ketidakpastian Institusi: Dampak Dinamis pada Pasar Saham Indonesia - Ilham Wahyu Firmansyah; Syofriza Syofyan (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study rigorously examines the dynamic effects of fiscal policy, monetary policy, and institutional quality on the performance of the Indonesian stock market in both the short run and the long run. Fiscal policy is represented by government revenue, government expenditure, and central government debt, while monetary policy is proxied by the interest rate, exchange rate, and broad money supply (M2). Institutional quality is captured by the Worldwide Governance Indicators (WGI). The analysis employs a quantitative approach using quarterly time-series data spanning from Q1 2010 to Q4 2024. To investigate long-run relationships and short-run adjustment dynamics among the variables, this study applies the Autoregressive Distributed Lag (ARDL) Bounds Testing Approach, which is well suited for variables with mixed orders of integration.  The empirical results confirm the existence of a robust long-run cointegration relationship between macroeconomic policies, institutional factors, and stock market performance. In the long run, central government debt, government expenditure, and exchange rate depreciation exert a significant negative impact on the stock market, supporting the crowding-out hypothesis and highlighting Indonesia’s vulnerability to external shocks. In contrast, government revenue and M2 have a statistically significant positive effect, indicating the importance of fiscal capacity and market liquidity in supporting stock market growth. Interest rates and inflation are found to be insignificant, suggesting that investors place greater emphasis on liquidity conditions and exchange rate stability rather than conventional price-based policy instruments. Short-run dynamics reveal a strong and rapid error-correction mechanism, indicating swift market adjustments that occasionally exhibit overshooting behavior. Furthermore, the WGI variable displays pronounced oscillatory effects, reflecting uncertainty premiums and investor learning in response to institutional quality changes.